Perancangan Sistem E-Learning Berbasis Web pada World Vision Indonesia - Agus Putranto (Bina Nusantara University, 2012)
World Vision Indonesia has several training programs with a very large total cost for 936 employees located in various parts of Indonesia, so that the manual training is considered less effective. Therefore, this research is conducted to design a learning management system application that supports the training process within the organization, and determine the needs for training materials. This research implemented strategyanalysis based on matrix EFE, IFE, SWOT, IE, and QSPM, as well as analysis and design of materials using Addie model. Meanwhile the design used a structured design method or OOAD. This research resulted in an application that supports the learning management system training process within the organization, provides accessible training materials by all employees at any time, and provides various features that creates training activities more effectively. The implementation of learning management system supports the company's strategy primarily to improve the quality of employees as well as reduces communication barriers between trainers and trainees both within and outside of training time.